Expression of Insoluble Influenza Neuraminidase Type 1 (NA1) Protein in Tobacco - Pua, Teen Lee; Loh, Hwei San; Massawe, Festo; Tan, Chon Seng; Omar, Abdul Rahman (Journal of Tropical Life Science, 2012)
The avian influenza virus, particularly H5N1 strain, is highly virulent to poultry and mankind. Several expression systems, like yeast, baculovirus and mammalian cells, have been adopted to produce vaccine candidate for this lethal disease. The present research aimed at developing a recombinant vaccine candidate, neuraminidase type 1 (NA1), for the Malaysia isolate of H5N1 in Nicotiana benthamiana. The NA1 gene was fused directly in-frame in cowpea mosaic virus (CPMV)-based pEAQ-HT vector with C-terminal polyhistidine-tag incorporated to ease the subsequent purification step. The expression of the NA1 gene in tobacco was confirmed at RNA and protein levels at 6 days post-infiltration (Dpi). From the insoluble fraction of the protein, a recombinant glycosylated NA1 protein with a molecular weight of ~56 kDa was immunogenically detected by a specific anti-NA polyclonal antibody. We report for the first time the insolubility of the plant-made NA1 protein where a native sequence was used for its expression. This study signifies the necessity of the use of optimised sequences for expression work and provides great opportunity for the exploration of plant-manufactured NA1 protein as vaccine candidate.